Influence of crumb rubber gradation on asphalt-rubber properties - Neto, Silvrano Adonias Dantas (2006)
Asphalt rubber is a material produced by the incorporation of crumb rubber obtained from ground tires in straight asphalt and its properties are influenced by the components properties. The crumb rubber gradation is one of the variables which have a significant influence on asphalt rubber properties. Thus, this work studies the influence of crumb rubber gradation on the asphalt rubber properties expressed by penetration, rotational viscosity (using the Brookfield viscometer), resilience and softening point. Test samples were produced with a 50/70 penetration grade straight asphalt and a crumb rubber obtained by the grinding process which basically consists in a tearing and crushing the old tires at ambient temperature. The digestion time was 60 minutes and the digestion temperature was 170 ºC. The results show that the rotational viscosity and the resilience are the properties most affected by the crumb rubber. It was also observed that the increase of the crumb rubber specific surface (fine crumb rubber) produces asphalt rubber with higher viscosity and lower resilience. The use of coarse crumb rubber influences mainly the resilience.